Marine Cyclic Guanidine Alkaloids Monanchomycalin B and Urupocidin A Act as Inhibitors of TRPV1, TRPV2 and TRPV3, but not TRPA1 Receptors - Korolkova, Yuliya (Mar Drugs, 2017)
Marine sponges contain a variety of low-molecular-weight compounds including guanidine alkaloids possessing different biological activities. Monanchomycalin B and urupocidin A were isolated from the marine sponge Monanchora pulchra. We found that they act as inhibitors of the TRPV1, TRPV2, and TRPV3 channels, but are inactive against the TRPA1 receptor. Monanchomycalin B is the most active among all published marine alkaloids (EC(50) 6.02, 2.84, and 3.25 μM for TRPV1, TRPV2, and TRPV3, correspondingly). Moreover, monanchomycalin B and urupocidin A are the first samples of marine alkaloids affecting the TRPV2 receptor. Two semi-synthetic urupocidin A derivatives were also obtained and tested against TRP (Transient Receptor Potential) receptors that allowed us to collect some data concerning the structure-activity relationship in this series of compounds. We showed that the removal of one of three side chains or double bonds in the other side chains in urupocidin A led to a decrease of the inhibitory activities. New ligands specific to the TRPV subfamily may be useful for the design of medicines as in the study of TRP channels biology.